2022
DOI: 10.3389/fnut.2022.927212
|View full text |Cite
|
Sign up to set email alerts
|

The association between sugar-sweetened beverages and milk intake with emotional and behavioral problems in children with autism spectrum disorder

Abstract: BackgroundEmotional and behavioral problems are common in children with autism spectrum disorder (ASD). It's still unclear whether children with ASD have abnormal sugar-sweetened beverages (SSBs) and milk intake and whether this abnormality will affect their emotions and behavior remains unclear. The current study aims to investigate the association of SSBs and milk intake with emotional and behavioral problems in children with autism spectrum disorder (ASD).Methods107 children with ASD and 207 typical develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Additional behavioral and emotional symptoms that improved on a Low Sugar diet included attention, irritability, anxiety, and cognition. This is consistent with a study on children with ASD where researchers observed an association between a higher consumption of sugar sweetened beverages and emotional problems scores [76].…”
Section: Low Sugar Dietsupporting
confidence: 92%
“…Additional behavioral and emotional symptoms that improved on a Low Sugar diet included attention, irritability, anxiety, and cognition. This is consistent with a study on children with ASD where researchers observed an association between a higher consumption of sugar sweetened beverages and emotional problems scores [76].…”
Section: Low Sugar Dietsupporting
confidence: 92%
“…Hair loss is generally regarded as the clinical manifestation of these diseases. Moreover, SSB intake is thought to promote emotional problems [ 30 , 31 ]. A cohort study confirmed an adverse effect of sugar intake from sweetened food and beverage on long-term psychological health [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research in China has also reported that SSB consumption is highest in the 13–29-year-old age group (22.38%) [ 23 ]. Current studies indicate that excessive SSB consumption is associated with chronic diseases, obesity, tooth decay, and emotional problems [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. As a major dietary source of added sugars [ 34 ], SSBs may be a potential risk factor for MPHL.…”
Section: Introductionmentioning
confidence: 99%
“…Many sugar-sweetened beverages (SSBs), such as colas, contain phosphoric acid, and increased consumption of SSBs is associated with stronger and more difficult emotional problems in ASD (Ref. 90 ). In addition, baking powder, chocolate, cocoa and beer are common sources of dietary phosphate that may contribute to excessive phosphate intake (Ref.…”
Section: Asd Phosphate Additives and Ultraprocessed Foodmentioning
confidence: 99%